Effectiveness of Online-Based Physics Learning During Pandemic - Hardani Hardani; Alpiana Hidayatulloh; Alpi Zaidah; Muh. Iman Darmawan (Jurnal Pembelajaran Fisika, 2020)
This study aims to analyze the effectiveness of online learning in physics subjects. This study uses qualitative descriptive methods and data obtained by providing evaluation and observation tests. The subject of this study was grade X as many as 18 students. To find out the effectiveness of online physics learning, an evaluation was carried out with an essay test of 5 questions and an observation sheet of 5 types of assessment. Then the results were analyzed by descriptive qualitative.  Based on the results of the analysis, 27.8% got the moderate category, 61.1% got low scores and 11.1% got the very low category. Then for the student activity assessment sheet, there is 14.5% student attendance, 13% of students pay attention to the teacher's explanation, 2.8% of students and do other activities actively during the learning process, and 15% collect assignments. Online learning is ineffective in pandemics. The cause of the low percentage is due to the many obstacles faced by students in participating in online learning, one of which is the lack of supporting facilities for online learning.Keywords: Effectiveness, Physics Learning, Online Learning, PandemicDOI: http://dx.doi.org/10.23960/jpf.v8.n2.202006